Experience in introducing a new interactive format of lectures at clinical departments and the attitude of students towards them - O.B. Yaremenko; D.V. Dobrianskyi; I.P. Tarchenko; A.V. Meliksetian; D.V. Fedkov (Medičnì Perspektivi, 2021)
The modern model of education and the present conditions demand of the teacher to choose the latest teaching methods. The teacher is no longer the main source of information, he should manage education, implementing competence-based study methods. In order to achieve this, the latest teaching methods are introduced in Bogomolets National Medical University with the new lecture frameworks. Changing the lecture style at a medical universities and, in particular, using the modern lecture educational technologies provide important conditions for improving training future doctors. As Bogomolets National Medical University experience shows, this provides opportunity for turning traditional lectures into interactive lessons to increase students’ interest, to provide improved material perception through the dialogue between the lecturer and students. The article presents the results of surveys of 387 students conducted at the Department of Internal Medicine №3, as well as generalized information regarding students’ evaluation of changes in the lecture framework and the implementation of new training methods in Bogomolets National Medical University. According to the survey results, most students are satisfied with the quality of the updated lecture frameworks at the therapeutic departments. The main characteristics of the lectures that teachers need to pay attention to in order to improve the lecture quality have been analyzed separately. In the view of the students, the best features of the lectures are: actuality, availability of material, structure and laconicism, informativeness, interactivity, video footage using, practical orientation of the presentation, illustration and sufficient number of visuals, an opportunity to be engaged in dialogue with lecturer. Students find traditional attendance control useless, the majority of respondents supported free lecture attendance.